Fiume, paesaggio, difesa del suolo - Michele, Ercolini (Scuole di dottorato, 2007)
On 10 and 11 May 2006 the international conference on the theme "River, landscape and land conservation. Overcoming emergencies and grasping opportunities" was held in the main lecture hall of Florence University. The initiative was promoted and organised by the PhD course in Landscape Design - Professor Giulio G. Rizzo, Dr. Michele Ercolini - and by the Master degree course in Landscaping - Professor Guido Ferrara - of the University of Florence. The majority of the addresses presented during the two days of work, and included in this book, were characterised by the cultural and scientific input of the initiative, in other words the attempt to transform a "system of demands" (namely the requirements of land conservation) into a "system of opportunities" for the design of new landscapes.